Motion Graphic sebagai Media Dakwah - Damayanti, Nurbaiti Dwi; Muhaemin, Enjang; Rojudin, Rojudin (Tabligh: Jurnal Komunikasi dan Penyiaran Islam, 2024)
This paper aims to know how the role of motion graphics in the process of delivering da'wah, to find out about how to use motion graphics as a medium of da’wah, elements of motion graphics that are applied, and the message of da'wah on videos in 'Bener Gitu?' YouTube channel. The method used is a qualitative research method with descriptive analysis. The results of this study indicate that motion graphic is a scientific media that can be used as a da’wah medium. There are two elements used in the video making process, there are audio elements and visual elements. The object transformations used in making videos include position, rotation, scale, and opacity transformations. The message contained in the video is about sharia and akhlaq and the importance of tolerance between other religions and other Muslims.